Prognostic Significance of Organ Dysfunction in Cats With Polytrauma - Murgia, Elsa; Troia, Roberta; Bulgarelli, Cecilia; Pelizzola, Marco; Foglia, Armando; Dondi, Francesco; Giunti, Massimo (Frontiers in Veterinary Science, 2019)
Polytrauma is a common emergency condition in small animals and is frequently associated to higher morbidity and mortality rates compared to minor trauma. Multiple Organ Dysfunction Syndrome (MODS) is a major complication of extensive traumatic injury, requiring intensive monitoring for the high risk of early and late death. Little is known about the pattern and prognostic impact of MODS in feline polytrauma. The current study aimed to prospectively evaluate the occurrence and the prognostic significance of organ dysfunction in a population of polytraumatized cats. Cats with polytrauma requiring intensive care unit hospitalization were included and divided according to outcome (survivors/non-survivors). Clinical and clinicopathological data, including scores of disease severity [Animal Trauma Triage Score (ATTS), APPLEfast and APPLEfull], selected organ dysfunction and presence of MODS were evaluated upon admission, and analyzed in respect to mortality. Non-parametric statistics was performed. P<0.05 was considered significant. Thirty-eight cats met the inclusion criteria: 8/38 (21%) had penetrating trauma, while 30/38 (81%) had blunt trauma. The overall in-hospital mortality was 37% (14/38). Cats with evidence of MODS upon admission had significantly greater frequencies of death compared to cats without MODS (9/14 vs 2/24 P=0.0004). The presence of hemostatic dysfunction, respiratory dysfunction and MODS upon admission were significantly associated to mortality in the univariate logistic regression analysis (P=0.002, P˂0.0001, P=0.0002, respectively). The values of APPLEfast, APPLEfull and ATTS were independently associated to a higher risk of death and positively correlated with the number of dysfunctional organs (P=0.025, P=0.004, P=0.003, r=0.57, P=0.0002; r=0.59 P=0.0001; r=0.55, P=0.0003, respectively). MODS is a common complication of feline polytrauma and its development is associated with increased disease severity and worse outcomes. Presence of hemostatic dysfunction and respiratory dysfunction upon admission seem to be associated with a higher risk of death. Scores of disease severity confirm their usefulness to early predict in-hospital mortality and development of organ dysfunction.